Algorithms, probability, networks, and games : scientific papers and essays dedicated to Paul G. Spirakis on the occasion of his 60th birthday /: scientific papers and essays dedicated to Paul G. Spirakis on the occasion of his 60th birthday. (2015) - Unknown
No abstract available